Azetidine- and N-carboxylic azetidine-iminosugars as amyloglucosidase inhibitors: synthesis, glycosidase inhibitory activity and molecular docking studies1. Issue 23 (21st June 2015) - Gavale, Kishor S.; Chavan, Shrawan R.; Khan, Ayesha; Joshi, Rakesh; Dhavale, Dilip D.
<x xml:space="preserve">Abstract</x> Azetidine and an unprecedented N-carboxylic azetidine iminosugars were synthesized from d-glucose, which showed prominent amyloglucosidase inhibitory activity.